2006
DOI: 10.1021/jm051296s
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small Molecule Integrin αvβ3 Antagonists as Novel Anticancer Agents

Abstract: Integrin alphavbeta3 has been implicated in multiple aspects of tumor progression and metastasis. Many tumors have high expression of alphavbeta3 that correlates with tumor progression. Therefore, alphavbeta3 receptor is an excellent target for drug design and delivery. We have discovered a series of novel alphavbeta3 antagonists utilizing common feature pharmacophore models. Upon validation using a database of known alphavbeta3 receptor antagonists, a highly discriminative pharmacophore model was used as a 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 52 publications
1
76
0
Order By: Relevance
“…Thiazolidin-4-one derivatives have been reported for broad spectrum of biological activities such as antioxidant (2), anticancer (3,4), anti-inflammatory (5, 6), antimicrobial (7,8), anti-HIV (9, 10), antiviral (11), anticonvulsant (12,13), and antihypertensive (14) activities. Mechanisms of thiazolidin-4-one and related heterocycles for anticancer activity may be associated with their affinity to anticancer biotargets, such as non-membrane protein tyrosine phosphatase (SHP-2) (15), JNK-stimulating phosphatase-1 (JSP-1) (16) tumor necrosis factor TNF-a (17), antiapoptotic biocomplex Bcl-X L -BH3 (18) and integrin a v b 3 (19), etc. On the other hand, azoles are proven chemotherapeutic agents.…”
mentioning
confidence: 99%
“…Thiazolidin-4-one derivatives have been reported for broad spectrum of biological activities such as antioxidant (2), anticancer (3,4), anti-inflammatory (5, 6), antimicrobial (7,8), anti-HIV (9, 10), antiviral (11), anticonvulsant (12,13), and antihypertensive (14) activities. Mechanisms of thiazolidin-4-one and related heterocycles for anticancer activity may be associated with their affinity to anticancer biotargets, such as non-membrane protein tyrosine phosphatase (SHP-2) (15), JNK-stimulating phosphatase-1 (JSP-1) (16) tumor necrosis factor TNF-a (17), antiapoptotic biocomplex Bcl-X L -BH3 (18) and integrin a v b 3 (19), etc. On the other hand, azoles are proven chemotherapeutic agents.…”
mentioning
confidence: 99%
“…The authors later confirmed this hypothesis using a series of analogues in which this distance was varied. 62 This study showed that shortening the compound by one carbon (compound 15) caused a greater than 100-fold decrease in potency, and lengthening by one carbon (compound 16) was also unfavorable, resulting in micromolar inhibition, Figure 9. …”
Section: Introductionmentioning
confidence: 91%
“…The optimal conditions, found for the reaction of 5-phenyl- [1,2,5]oxadiazolo [3,4-b]pyrazine (1a) with pyrroles, indoles and carbazoles, have been applied for the C-C coupling of 5-(hetero)aryl- [1,2,5]oxadiazolo [3,4-b]pyrazines (1b-d) with the same nucleophiles. Highly electrophilic azines (1a-d) have been found to react smoothly with pyrroles (7,8), indoles (11)(12)(13) and carbazoles (17)(18)(19) at room temperature to give the corresponding products 9-10, 14-16 and 20-22 in 71% , 87% and 76% yields, respectively. It is worth noting that structures of the SN Hproducts 9a, 10d, 14a, 21a, 22a and 22c have been established unequivocally by X-ray crystallography (Figs.…”
Section: Synthesismentioning
confidence: 99%
“…10 Also, the addition of ferrocenyl lithium or cymantryl lithium at C(6) of furazano [3,4-b]pyrazines 1, followed by oxidation of the intermediate σ H -adducts, affords the corresponding metallocene derivatives 4 and 5 (Scheme 1). 11 Finally, 6-styryl-5-(hetero)aryl-furazano [3,4- [3,4-b]pyrazines.…”
Section: Introductionmentioning
confidence: 99%